The effect of social participation on depressive symptoms in older women adults in China: A tracking survey database - Zicheng Jiang; Jing Deng; Yue Fan; Qianwen Song; Qi Cui; Huan Liu; Wenjun Que (PLoS ONE, 2025)
Background Under the context of active aging, older women face prominent mental health risks due to their dual vulnerability stemming from biological characteristics and social roles. Given the existing practical bottlenecks in current research namely, unclear mechanisms regarding how social participation alleviates geriatric depression and insufficient studies on population heterogeneity. It is important to analyze the impact of social participation on depressive symptoms of older women in China and to implement corresponding policy systems. Methods: Based on the 2018 health and old-age care tracking survey database in China, 3047 subjects older female were included (mean age = 69.46 years).Depressive symptoms were measured using the CESD-10 depression scale from the database, and 11 categories of social activity questionnaires were utilized to reflect the level of social participation. The impact of social participation on the depressive symptoms of older women in China was empirically analyzed using the common least squares (OLS) and two-stage least squares (2SLS) methods, and tested the endogenous and robustness of the subjects, the heterogeneity of age and urban-rural areas, and the mediating effect of self-rated health were tested using the sobel method. Results: Social participation improved the depressive symptoms of older women(β=-0.789, P < 0.01), and the variable method confirmed the estimated results through the endogeneity and robustness tests. At the same time, there was age and urban-rural heterogeneity. Social participation has a greater impact on depression symptoms in older adults 60–80 + than 80 + , and in urban areas than in rural areas. And social participation indirectly affected depression through self-assessment of health, and the indirect effect accounted for 21.4% (β = -0.139, P < 0.01). Conclusion: In the process of actively dealing with the aging of the population, the older women should be actively encouraged to participate in social activities such as community volunteering and hobby activities. According to the physical and mental development characteristics of different older groups, the government should formulate targeted social participation policies and improve relevant facilities for the elderly and the old-age security system.